Intravenous immunoglobulin treatment in multiple sclerosis: A prospective, rater‐blinded analysis of relapse rates during pregnancy and the postnatal period. (1st June 2018) - Winkelmann, Alexander; Rommer, Paulus Stefan; Hecker, Michael; Zettl, Uwe Klaus
Summary: Background: Multiple sclerosis (MS) affects predominantly young women. Currently available disease‐modifying drugs have neither been approved during pregnancy nor nursing. Aims: Evaluating the effect of treatment with intravenous immunoglobulin (IVIg) in MS patients with desire to have a baby. Methods: In all, 70 MS patients were either treated with IVIg before conception, during first trimester of pregnancy and 12 months postnatal (group I, n = 38) or started IVIg after delivery for 12 months (group II, n = 23) or were untreated (group III, n = 9). Relapse rates and disease progression were analyzed. Results: Pre‐gestational relapse rates differed between groups. Lowest relapse rates were observed during late pregnancy, followed by an elevated relapse rate after delivery compared to the pre‐pregnancy year and the first trimester. Only in group I, the postnatal relapse rate did not exceed the relapse rate before conception. IVIg treatment did not influence disease progression after delivery. Conclusions: In MS patients, IVIg treatment during and/or after delivery is an option to reduce the incidence of relapses during pregnancy and the postnatal period. Surprisingly, untreated patients becoming pregnant showed an increase in the relapse rate in the first trimester compared with the pre‐gestational period. How alterations of hormone status during pregnancy affect disease activity in MS has to be further investigated.